Implementation and evaluation of the Victorian Suicide Register - Georgina Sutherland; Allison Milner; Jeremy Dwyer; Lyndal Bugeja; Alan Woodward; Jo Robinson; Jane Pirkis (Elsevier, 2018)
Abstract Objective: The Victorian Suicide Register (VSR) is a state‐based suicide surveillance system that contains detailed information on people who die by suicide and the circumstances surrounding their death. In this paper, we provide an overview of the VSR and then describe the evaluation, which used the Centres for Disease Control and Prevention guidelines for surveillance system evaluation as a framework. Methods: The evaluation drew on three data sources to assess whether the VSR: i) embodies the attributes of a good public health surveillance system; and ii) can be used to inform community‐based suicide prevention efforts. Results: There was a high level of acceptability and enthusiasm for having an accessible data collection that can stimulate local action on suicide prevention planning. One of the key challenges identified was data quality, particularly around those data collected in the course of death investigations that are not designed for surveillance purposes. Conclusion: The VSR fills an important gap in the sustained and systematic collection of comprehensive information on suicide, with some key challenges identified. Implications for public health: Findings from the evaluation provide important strategic information for national and international jurisdictions seeking to establish their own suicide registers.